Preparation of dendrimer amphiphiles and in situ loading of catalytic noble metal nanoclusters
By designing a dendritic amphiphilic polymer and using the high internal comparison emulsion method, the problem of difficult to maintain the activity and selectivity of noble metal nanoclusters is solved, and high-quality and uniform preparation of noble metal nanoclusters is achieved, with high efficiency catalysis and good recovery.
Patent Information
- Application Number
- CN202310272392.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-03-17
AI Technical Summary
The prior art is difficult to prepare high-quality, highly active precious metal nanocluster catalysts, especially in maintaining catalytic activity and selectivity.
A dendritic amphiphilic polymer was designed and synthesized, and the loaded precious metal nanoclusters were modulated by the high internal comparison emulsion method. The emulsion was stabilized at a wide spectrum pH using the polyphilicity and self-assembly ability of the dendritic polymer to achieve efficient preparation of nanoclusters.
The preparation of high-quality precious metal nanoclusters is achieved, high catalytic activity and selectivity is maintained, and the specific surface of the material is increased under partial acid conditions, ensuring the uniformity and efficiency of the nanoclusters.
Smart Images

Figure CN116376040B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials, and specifically relates to a preparation method and application of carrier-based noble metal nanoclusters modulated by a type of dendritic amphiphilic polymer. Background Art
[0002] Precious metal nanoparticles and nanoclusters are an important type of catalyst, among which smaller metal nanoclusters are even more important. This is because the unique size of metal nanoclusters brings unique properties such as catalytic activity related to the quantum confinement effect, which the corresponding metal nanoparticles may not have; ultra-small metal nanoclusters have a surface area exceeding 100%, and their ultra-high surface area can provide more catalytic active sites, which can improve the atomic catalytic efficiency.
[0003] The key to preparing metal nanoclusters is the selection and design of metal ligands and kinetic regulation. At present, high-quality metal nanoclusters can only be prepared by a large number of strong ligands under specific kinetic conditions. The catalytic activity of such metal nanoclusters stabilized by strong ligands will be significantly reduced, and the catalytic spectrum will be narrowed. The possible benefit is that the catalytic selectivity may be improved. How to obtain highly active broad-spectrum noble metal nanocluster catalysts is still one of the important challenges at present.
[0004] Suitable ligands can improve the catalytic activity and selectivity of precious metals and even change the reaction mechanism to obtain completely different products. This is because the electron donating / withdrawing ability of the ligand can directly change the electronic microenvironment on the surface of the metal catalyst, resulting in changes in the affinity for the substrate or the stability of the reaction intermediates. In special cases, ligands can make the activity of metal catalysts much higher than that of naked metals. Of course, the spatial morphology of the ligand can also play some special roles. For example, when using rigid and bulky monothiol ligands to stabilize metal particles, due to steric repulsion, only a few ligands can approach the metal surface, resulting in a large amount of metal surface not passivated by thiol, thus showing higher catalytic activity. Methods such as ligand mismatching, ligand replacement, or sintering to remove ligands are also used to improve catalytic activity. At present, these methods still have great limitations. The solubility of the ligand is also an important parameter, which is the main factor determining the application scenario of the catalyst. For example, to make the catalyst usable in the aqueous phase, the ligand is preferably hydrophilic. Polymers are usually multi-ligands, and the metal nanoparticles modulated by them are usually highly active. However, polymers are generally weak ligands and can hardly modulate metal nanoclusters. This requires chemical design of polymer ligands. On the other hand, the unique self-assembly ability, conformational transformation ability and easy processing of polymers enable them to form ordered structures on a larger scale, which may play a unique role in catalyst loading.
[0005] At present, most chemical products in industry involve the use of catalysts in the production process, and a considerable part of them are heavy metal catalysts. Due to environmental protection, quality and cost requirements, about 68% of the catalysts are currently recyclable supported catalysts. Some supports can also affect the catalytic mechanism and catalyst activity like ligands. The specific surface area, mechanical strength and availability of the support are also important parameters. Support design is also one of the current research topics. Supports can also usually inhibit metal particle agglomeration and aging.
[0006] High internal phase ratio emulsion polymerization can conveniently provide porous polymer materials. This method can be combined with macromolecular surfactants to conveniently prepare supported metal nanoparticles. High internal phase ratio emulsion refers to a type of emulsion with a dispersed phase volume fraction of more than 74.05%. Further increasing the dispersed phase volume fraction will cause the droplets to squeeze each other, and the continuous phase will gradually become a film. The liquid film is polymerized and solidified, and the water droplet dispersed phase is removed to obtain a porous material, and the surface of the material is expressed by the surfactant. We pointed out in our previous report (Chinese patent: ZL 201510155126.0) that when the surfactant is a dendrimer with a large molecular weight, it can be firmly expressed on the surface and become a functional surface; further, if metal nanoparticles are wrapped in the dendrimer surfactant, a supported catalyst is formed, and the catalyst is almost all on the surface. Dendrimer surfactants are very suitable for this because dendrimers are more suitable for loading metal nanoparticles.
[0007] Direct modulation of high-quality and highly active supported noble metal nanoclusters by dendrimers has not been disclosed. Summary of the invention
[0008] The primary purpose of the present invention is to design and synthesize a dendritic amphiphilic polymer that needs to simultaneously meet the following requirements: (1) have a strong ability to modulate oil-in-water emulsions, (2) play a role as a metal ligand, and (3) stabilize the emulsion under a wide pH spectrum so that the dendrimer can exist as a single molecule template, thereby modulating high-quality precious metal nanoclusters.
[0009] The second purpose of the present invention is to use the dendritic amphiphilic polymer to prepare various types of loaded precious metal nanoclusters through a high internal phase ratio emulsion method.
[0010] The third object of the present invention is to use the nanocluster as a highly efficient, broad-spectrum, recyclable catalytic material.
[0011] To achieve the above object, the solution of the present invention is:
[0012] 1. Preparation of a type of dendritic amphiphilic polymer, namely dendritic amphiphile
[0013] The preparation of dendritic amphiphiles comprises the following steps:
[0014] (1) PEI, 4-glyceryl-2,2,6,6-tetramethylpiperidinyl nitroxide (GTEMPO) and long-chain alkyl glycidyl ether are dissolved in a common solvent (such as chloroform) and stirred for several hours. Components containing medium-strong ligands such as thioether small molecules (such as 3-methylthiopropionaldehyde), phosphine-containing small molecules (such as diphenylphosphobenzaldehyde), enamine-containing small molecules (such as N-glycidyl imidazole) or amidine-containing small molecules are added, and stirring is continued for several hours. The solvent is distilled off to obtain an oil-soluble macromolecule with multiple nitroxides.
[0015] (2) The above molecules are dissolved in a monomer containing styrene, a free radical initiator is added, and after deoxygenation, nitrogen-oxygen regulated active free radical polymerization is carried out. After the monomer is fully polymerized, the polymer is purified by a dissolution / precipitation method to obtain a dendritic amphiphilic polymer.
[0016] Preferably, the long-chain alkyl group in step (1) is an aliphatic or aromatic alkyl group containing 12 to 18 carbon atoms.
[0017] Preferably, in step (1), the molecular weight of PEI should be between 1000 and 2000 Daltons.
[0018] Preferably, in step (1), each PEI molecule is connected with the following medium-strong ligand groups: 3-6 thioether groups, 18-36 phosphine groups, 16-32 imidazole groups, and 12-36 amidine groups.
[0019] Preferably, in step (1), the amount of GTEMPO added should be 20-60% molar fraction of amino hydrogen on PEI; the amount of long-chain alkyl glycidyl ether used should be 0-50% molar fraction of amino hydrogen on PEI; and the sum of the two and the amount of the medium-strong ligand should be exactly equal to or slightly greater than 100% molar number of amino hydrogen.
[0020] Preferably, in step (2), the styrene monomer accounts for 100-60% by mole of the total monomer amount.
[0021] Preferably, the comonomer in step (2) should be selected from the type that both the monomer itself and its corresponding polymer have good oil solubility, such as (meth)acrylate, (meth)acrylamide, and the amount used is 0-40% by mole of the total amount of monomers.
[0022] Preferably, in the polymer finally obtained in step (2), the mass fraction of PEI in the entire molecule is 0.2-1%.
[0023] 2. Preparation of loaded precious metal nanoclusters
[0024] In-situ loading of catalytic noble metal nanoclusters is prepared by using the above-mentioned dendritic amphiphile through a high internal phase ratio emulsion method, comprising the following steps:
[0025] (1) A high internal phase ratio emulsion in water-in-oil is prepared using a dendritic amphiphilic polymer as a surfactant. The oil phase is composed of an oil-soluble olefin monomer, a crosslinking agent, a free radical initiator and a dendritic amphiphilic polymer, and the water phase is composed of a newly prepared buffer solution containing silver ions, chloroaurate or chloropalladate. A large amount of water phase is dropped into a small amount of oil phase under strong stirring to form a high internal phase ratio emulsion. After the emulsion is formed, it is heated to polymerize the oil phase, and then the water phase is removed by Soxhlet extraction with ethanol to obtain a through-hole material loaded with precious metal nanoclusters.
[0026] (2) If the noble metal is platinum, the first step is basically still prepared according to the above method, the pH of the aqueous phase is 4.5-5.5, but the aqueous phase does not contain metal species, the obtained porous material is purified and crushed, and then put into an aqueous solution containing platinum ions, and a reducing agent is added dropwise under stirring. Filter, wash with alcohol, and dry to obtain a through-hole material loaded with platinum nanoclusters.
[0027] Preferably, in steps (1) and (2), N: noble metal ion = 24:1 to 45:1 (molar ratio, N is the nitrogen atom in the dendritic amphiphilic polymer).
[0028] Preferably, in steps (1) and (2), the mass fraction of the dendritic amphiphilic polymer in the oil phase is 15-35%.
[0029] Preferably, in steps (1) and (2), the volume of the aqueous phase accounts for 74-83% of the total volume of the emulsion.
[0030] Preferably, in step (1), the pH of the buffer solution is 5.0-7.4.
[0031] 3. Application and reuse of catalysts
[0032] The catalyst can be used for aqueous phase reactions or polar oil phase systems. Generally, the through-hole material is crushed and placed in a Teflon bag with about 45 micron holes (when used for aqueous phase reactions, hydrophilic porous materials should be used) and then put into the reaction system. After the reaction is completed, the bag is directly taken out and used for the next reaction.
[0033] Due to the adoption of the above scheme, the beneficial effects of the present invention are:
[0034] (1) The dendrimer can directly prepare loaded precious metal nanoclusters in one pot.
[0035] (2) Since the molecular weight of the dendrimer is very large and the migration energy barrier is very high, it is unlikely to fall off during use.
[0036] (3) The noble metal nanoclusters stabilized by weak ligands were achieved, ensuring the high catalytic activity of the nanoclusters.
[0037] (4) They can be synthesized under slightly acidic conditions, which not only increases the specific surface area of the material but also enables the dendrimer to function as a single-molecule template, thereby modulating metal nanoclusters with more uniform sizes. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Example 1 Transmission electron microscopy images of gold nanoclusters loaded on porous carriers, with scale bars of 50 nm (left) and 10 nm (right).
[0039] Figure 2 . Fluorescence confocal micrographs of the emulsion stabilized by the dendritic amphiphilic polymer of Example 1 under laser irradiation at 405 (left) and 488 nm (right).
[0040] Figure 3 Example 1 UV / visible spectrum of 4-nitrophenol during catalytic reduction (left) and the apparent rate constant calculated therefrom (right). DETAILED DESCRIPTION
[0041] The present invention relates to the direct modulation of high-quality loaded precious metal nanoclusters by a high internal phase ratio emulsion method using a dendritic amphiphilic polymer and its catalytic application. The dendritic amphiphilic polymer is obtained by introducing an oil-soluble component into a branched polyethyleneimine (PEI) having a molecular weight of 1000 to 2000 Daltons. The weight fraction of PEI in the dendritic amphiphilic polymer is between 0.2% and 1%. At the same time, a certain amount of thioether, triphenylphosphine or enamine-containing heterocycle is covalently introduced into PEI. The obtained dendritic polymer is used as an oil-soluble surfactant to modulate an oil-in-water high internal phase ratio emulsion, which is stable within the pH range of 11-4.0. A porous through-hole material can be obtained by heating to polymerize the oil phase and removing the water phase. When the aqueous phase buffer contains silver ions, chloroaurate and chloropalladate, the surface of the through-hole material is respectively loaded with silver nanoclusters, gold nanoclusters and palladium nanoclusters. The dendritic polymer exists as a single molecule template at low pH and can modulate uniform precious metal nanoclusters. For the synthesis of platinum nanoclusters, the through-hole material is first prepared, crushed, mixed with an aqueous solution of chloroplatinate, and treated with a reducing agent. These supported catalysts have high catalytic activity and good recyclability.
[0042] The present invention will be further described below with reference to the embodiments.
[0043] Example 1
[0044] Synthetic dendrimers
[0045] Step 1. PEI (molecular weight 2000 Dalton, 0.25 g, 5.8 mmol NH), hexadecyl glycidyl ether (0.695 g, 2.32 mmol, 0.4 molar equivalent of amino hydrogen) and 4-glyceryl ether-2,2,6,6-tetramethylpiperidinyl nitroxide (GTEMPO) (0.66 g, 2.9 mmol, 0.5 equivalent of amino hydrogen) were dissolved in chloroform (1.5 mL) and stirred at room temperature for 24 h. 3-Methylthiopropionaldehyde (0.0725 g, 1.2 equivalent of amino hydrogen) was added and stirred for 24 h. The solvent was removed to obtain the product.
[0046] Step 2. Mix the above product (1.68 g, 2.9 mmol of nitroxide free radical), azobisisobutyronitrile (0.285 g, 0.6 molar equivalent of nitroxide free radical) and styrene (90.5 g, 300 molar equivalent of nitroxide free radical) to form a solution, deoxygenate with nitrogen, heat at 70°C for 5 h, and then heat at 135-140°C for 68 h. Dissolve the product in chloroform and precipitate with 95% ethanol, repeat twice. Obtain 65 g of solid product (70.6%). Comprehensive elemental analysis, nuclear magnetic resonance and gel permeation chromatography analysis show that the structure of the product is PEI-S 4.7 @(C16) 19 -(PS 212 ) 23 (212 is the degree of polymerization of styrene, and the other subscripts represent the corresponding number of functional groups connected to each PEI, S represents sulfide, C16 represents hexadecyl glycidyl ether, and PS represents polystyrene).
[0047] Synthesis of supported gold nanoclusters (AuNC)
[0048] The PEI-S was added to a solution containing styrene (1 mL), divinylbenzene (1 mL), and azobisisobutyronitrile (15 mg). 4.7 @(C16) 19 -(PS 212 ) 23 (0.6 g, N content 0.054 mmol), stirred to form an oil phase. Add a freshly prepared chloroauric acid aqueous solution (containing Au 3+ 0.0017 mmol phosphate buffer (8 mL, pH 6.0) was added within 15 minutes. Stirring was continued for 15 minutes after the addition. The paste-like concentrated emulsion was placed in an oil bath at 70±5°C for 7 hours to solidify. The solid block was first washed with deionized water and then extracted and purified with 95% ethanol.
[0049] Test characterization. Take a small amount of sample, grind it in ethanol, and disperse it on the carbon film for transmission electron microscopy analysis. The results are as follows: Figure 1As shown, the size of the obtained gold nanoclusters was 1.8±0.3 nm.
[0050] The concentrated emulsion before polymerization (high internal phase ratio emulsion) was diluted with toluene and then analyzed by fluorescence confocal microscopy. It was found that the dispersed phase droplets were fluorescent ( Figure 2 ), which is emitted by PEI in the dendritic surfactant, indicating that the dendritic surfactant is at the oil-water interface.
[0051] Supported gold nanoclusters can be used for catalytic reactions.
[0052] Nitrogen was bubbled through an aqueous solution (100 mL) of NaBH4 (60 mmol / L) and 4-nitrophenol (0.06 mmol / L) for half an hour. The gold nanocluster carrier catalytic material (0.52 g, Au content: 0.1 mg) was then crushed and placed in a Teflon bag (with 45 micron hydrophilic holes on the bag), which was put into the bag and the timing was started. Samples were taken at regular intervals for UV / visible light scanning tests, and the tested samples were immediately returned to the reaction system to continue the reaction. The reaction progress was monitored until the absorption of the substrate at 400 nm was close to zero ( Figure 3 ). Lift out the bag and reuse it. Figure 3 The spectral data can be used to derive the rate constant k = 4.4 × 10 -3 / s. Based on the feed and k value, the operating frequency of the catalyst can be calculated to be 25.7 / h.
[0053] Example 2
[0054] The same method as in Example 1 was used, but the pH of the gold nanoclusters during synthesis was changed to 7.4, 6.0, 4.4 and 4.0 buffer solutions, and the specific surface area of the carrier and the size of the gold nanoclusters were tested. The results are shown in Table 1.
[0055] Table 1. Parameters of porous materials and sizes of gold nanoparticles or gold nanoclusters prepared under different pH conditions.
[0056]
[0057] a pH 7.4 and 6.0 (phosphate buffer), pH 5.0-4.0 (sodium dihydrogen phosphate-citrate buffer); b The data are calculated from literature (Macromolecules 1997, 30, 2151); c Measured by mercury intrusion porosimetry; d The ratio of the specific surface area measured by mercury intrusion porosimetry to the theoretically calculated PEI area; e Regulated by thioether-free dendrimers.
[0058] The results show that the lower the pH, the higher the specific surface area of the carrier material; at the same time, the surface area occupied by a single dendrimer of PEI is about twice the theoretically calculated projected area of a pure PEI sphere. This is because under acidic conditions, PEI is fully protonated and charged and repel each other, resulting in the existence of dendrimers as single-molecule templates. This single-molecule state is not only conducive to improving the specific surface area of the porous carrier, but also conducive to the formation of more uniform AuNC. However, when the pH is lower than 5.0, the metal ions are reduced slowly and it is difficult to completely reduce them, resulting in partial loss. At the same time, the affinity of the amino group to the gold atom becomes poor after protonation, resulting in the increase of the size of the gold particles. Therefore, the preparation of AuNC at pH 5.0-6.0 is the most ideal.
[0059] Example 3
[0060] The same method as in Example 1 was used, but the chloroauric acid in the aqueous phase was replaced with silver nitrate and ammonium chloropalladate in sequence to perform a similar synthesis. The obtained silver nanoparticles were 1.70±0.44 nm, and the palladium nanoparticles were 1.60±0.26 nm.
[0061] Example 4
[0062] Same as Example 1, but the aqueous phase does not contain any precious metal species. The synthesized porous through-hole material is crushed, and sodium chloroplatinate aqueous solution is added according to N:Pt=32:1. After fully mixing, a newly prepared sodium borohydride aqueous solution (the borohydride ion is more than 10 equivalents of platinum ions) is added. After 2 hours, the solid is filtered out. High-resolution transmission electron microscopy test shows that the particle size is 1.77±0.28nm.
[0063] Example 5
[0064] PEI (0.25 g, 5.8 mmol NH), diphenylphosphobenzaldehyde (1.3 g, 4.466 mmol, 0.77 equivalent of NH) and 4-glycerylether-2,2,6,6-tetramethylpiperidinylnitroxide (GTEMPO) (0.3 g, 1.32 mmol, 0.23 equivalent of amino hydrogen) were dissolved in chloroform (5 mL), stirred at room temperature for 5 h in a nitrogen atmosphere, and refluxed for 2 h. The chloroform was removed.
[0065] The above product (1.85 g, 1.32 mmol of nitroxide free radical), azobisisobutyronitrile (0.13 g, 0.6 molar equivalent of nitroxide free radical) and styrene (34.3 g, 250 molar equivalent of nitroxide free radical) were mixed to form a solution, deoxygenated by nitrogen, heated at 70°C for 5 h, and then heated at 135-140°C for 70 h. The product was dissolved in chloroform and precipitated with 95% ethanol, and repeated twice. 25 g of solid product (70%) was obtained.
[0066] Regulating gold nanoclusters. As in Example 1, the synthesis of gold nanoclusters was similarly regulated by replacing the sulfide-containing dendrimer with a phosphorus-containing dendrimer to obtain gold nanoclusters of 1.6±0.2nm.
[0067] Example 6
[0068] Under nitrogen protection, PEI (0.5 g, 11.6 mmol amine) and N,N-dimethylformamide dimethyl acetal (DMFDMA) (0.415 g, 3.49 mmol) in ethanol (3 mL) were stirred at room temperature for 6 hours. Samples were taken for NMR characterization. 1 H NMR (400MHz, CDCl3, ppm): 8.1-8.0 (m, 1H, NCHN), 2.8-2.4 (m, 25H, CH2N), 2.08 (d, 2H, CH2NCHN) and 1.96 (s, 15H, CH2NH, CH2NH2). Then, hexadecyl glycidyl ether (0.87g, 2.9mmol, 0.25 molar equivalent of amino hydrogen) and 4-glycerylether-2,2,6,6-tetramethylpiperidinyl nitroxide (GTEMPO) (1.14g, 5mmol, 0.43 equivalent of amino hydrogen) were poured into chloroform (8mL) solution and stirred at room temperature for 7 hours.
[0069] The living free radical polymerization of styrene monomer was carried out similarly to Example 1. On average, each PEI was connected with 20 polystyrene chains, and the degree of polymerization of each chain was 120.
[0070] The regulated synthesis of palladium nanoclusters was carried out similarly to Example 1 to obtain palladium nanoclusters of 1.5±0.3 nm.
[0071] The above description is only a description of the preferred embodiments of the present application, and is not intended to limit the scope of the present application. Any changes or modifications made by any person skilled in the art based on the above disclosed technical contents shall be deemed as equivalent effective embodiments and shall fall within the scope of protection of the technical solution of the present application.
Claims
1. A method for preparing a dendritic amphiphile, characterized in that: The preparation method comprises the following steps: (1) PEI, 4-glyceryl-2, 2, 6, 6-tetramethylpiperidinyl nitroxide free radical and long-chain alkyl glycidyl ether are dissolved in a common solvent and stirred for several hours, and a component containing a medium-strong ligand is continuously added, wherein the medium-strong ligand is a thioether small molecule, a phosphine-containing small molecule, an enamine-containing small molecule or an amidine-containing small molecule, and the stirring is continued for several hours, and the solvent is removed by distillation to obtain an oil-soluble macromolecule with multiple nitroxide free radicals; (2) The above macromolecules are dissolved in a monomer containing styrene, a free radical initiator is added, and after deoxygenation, nitrogen-oxygen regulated active free radical polymerization is carried out. After the monomer is fully polymerized, the polymer is purified by a dissolution / precipitation method to obtain a dendritic amphiphilic polymer.
2. The method for preparing a dendritic amphiphile according to claim 1, characterized in that: In step (1), the long-chain alkyl group is an aliphatic or aromatic alkyl group containing 12 to 18 carbon atoms.
3. The method for preparing a dendritic amphiphile according to claim 1, characterized in that: In step (1), The molecular weight of PEI should be between 1000 and 2000 Daltons; Each PEI molecule is connected with 3-6 medium-strong ligand groups: 3-6 thioether groups, 18-36 phosphine groups, 16-32 imidazole groups, and 12-36 amidine groups.
4. The method for preparing a dendritic amphiphile according to claim 1, characterized in that: In step (1), the amount of 4-glyceryl-2,2,6,6-tetramethylpiperidinyl nitroxide free radical added should be 20-60% of the molar fraction of amino hydrogen on PEI; the amount of long-chain alkyl glycidyl ether added should be 0-50% of the molar fraction of amino hydrogen on PEI; and the sum of the amount of 4-glyceryl-2,2,6,6-tetramethylpiperidinyl nitroxide free radical, long-chain alkyl glycidyl ether and medium-strength ligand should be exactly equal to or slightly greater than 100% of the molar number of amino hydrogen.
5. The method for preparing a dendritic amphiphile according to claim 1, characterized in that: In step (2), the styrene monomer accounts for 100-60% by mole of the total monomers; the monomers also include comonomers, and the comonomers are selected from the type that both the monomer itself and its corresponding polymer have good oil solubility, and the amount used is 0-40% by mole of the total monomers.
6. The method for preparing a dendritic amphiphile according to claim 1, characterized in that: In the final polymer obtained in step (2), the mass fraction of PEI in the entire molecule is 0.2-1%.
7. In-situ supported catalytic noble metal nanoclusters prepared by using the dendritic amphiphile prepared by the method according to any one of claims 1 to 6, characterized in that: The dendritic amphiphile is prepared by a high internal phase emulsion method, comprising the following steps: (1) A dendritic amphiphilic polymer is used as a surfactant to prepare an oil-in-water emulsion with a high internal phase ratio; the oil phase is composed of an oil-soluble olefin monomer, a crosslinking agent, a free radical initiator and the dendritic amphiphilic polymer, and the water phase is composed of a newly prepared buffer solution containing silver ions, chloroaurate or chloropalladate; a large amount of water phase is dropped into a small amount of oil phase under strong stirring to form a high internal phase ratio emulsion; after the emulsion is formed, it is heated to polymerize the oil phase, and then the water phase is removed by Soxhlet extraction with ethanol to obtain a through-hole material loaded with precious metal nanoclusters; (2) If the precious metal is platinum, the first step is still prepared according to the above method, the pH of the aqueous phase is 4.5-5.5, but the aqueous phase does not contain metal species. The obtained porous material is purified and crushed, and then put into an aqueous solution containing platinum ions, and a reducing agent is added dropwise under stirring; filtered, washed with alcohol, and dried to obtain a through-hole material loaded with platinum nanoclusters.
8. The in-situ supported catalytic noble metal nanoclusters according to claim 7, characterized in that: In step (1) to step (2), N: noble metal ion = 24:1-45:1, which is the molar ratio, and N is the nitrogen atom in the dendritic amphiphilic polymer; The mass fraction of the dendritic amphiphilic polymer in the oil phase is 15-35%; The volume of the aqueous phase accounts for 74-83% of the total volume of the emulsion.
9. The in-situ supported catalytic noble metal nanoclusters according to claim 7, characterized in that: In step (1), the pH of the buffer solution is 5.0-7.
4.
10. The in-situ supported catalytic noble metal nanoclusters as claimed in claim 7 are used as a highly efficient, broad-spectrum, recyclable catalytic material.
Citation Information
Patent Citations
A kind of precious metal nanoparticle modified porous carrier catalytic material and preparation method thereof
CN104815693B
Precious metal nanoparticle-modified porous carrier catalytic material and preparation method thereof
CN104815693A
Precious metal nanoparticle supported porous material catalyst and preparation method thereof
CN107952481A